Expanding the Use of Zymography by the Chemical Linkage of Small, Defined Substrates to the Gel Matrix - Kaberdin, Vladimir R.; McDowall, Kenneth J.

(untitled) (Genome Research, 2003)
In the postgenomic era, the comprehensive proteomic analysis of metabolic and signaling pathways is inevitably faced with the challenge of large-scale identification and characterization of polypeptides with a particular enzymatic activity. Previous work has shown that a wide variety of enzymatic activities of microbial, plant, and animal origin can be assigned to individual polypeptides using in-gel activity staining (zymography). However, a number of limitations, such as special substrate requirements, the lack of a standard procedure, and difficulties in distinguishing enzymes with overlapping activities have precluded the widespread use of zymography as a routine laboratory method. Here we demonstrate that, by employing small-defined substrates that are covalently attached to the gel matrix, we can largely overcome the aforementioned problems and assay readily a number of different classes of enzymatic activities within gels after standard SDS-polyacrylamide electrophoresis. Moreover, this development is compatible with the two-dimensional separation of proteins and thus has great potential in the high-throughput screening and characterization of complex biological and clinical samples.